New species of cave-dwelling cholevids (Cholevidae, Coleoptera) from Serbia - Ćurčić, Srećko; Brajković, Miloje; Mihajlova, Branislava (Macedonian Journal of Ecology and Environment, 2003)
Recently two species of cavernicolous cholevids have been described from west and southwest Serbia - Pholeuonopsis cvijici Ćurčić & Brajković from Potpećka Pećina Cave, village Potpeće near Užice, and Magdelainella bozidarcurcici Ćurčić & Brajković from Pećina in Potkapilija Cave, village Trudovo near Nova Varoš. From their phenetically closest congeners, these two new species are clearly distinct in many important respects such as: body size, the body length to breadth ratio, length to breadth ratios of some antennomerae, shape of pronotum, form of mesosternal carina, shape of elytra, the size of the scutellum, form of aedeagus, shape of paramerae and the different position of setae on the apex of the paramerae, as well as the form of the structures forming the inner sac of aedeagus. The new species of cave cholevids belong to the old phyletic lineages of the Tertiary origin, which are relict and endemic both to Serbia and the Balkan Peninsula.